IN VITRO-IN VIVO BIO-EQUIVALENCE CORRELATION STUDY OF METRONIDAZOLE, AND ITS BRANDS OF IMMEDIATE RELEASE TABLET UNDER BIO-WAIVER CONDITIONS - Ahmed, EM; Ibrahim, ME; Magbool, FF (Universal Journal of Pharmaceutical Research, 2020)
Objective: The aim of present study is to examine the in-vitro in-vivo correlation (IVIVC) of immediate release product. Metronidazole 500mg and its brands of immediate release dosage forms. Metronidazole is clearly classified into BCS class I, and could be evaluated under bio waiver conditions. Methods: The in vitro parameters employed were hardness, weight uniformity, friability, disintegration time, absolute drug content, dissolution rate (in 0.1 N Hydrochloric acid, phosphate buffer and acetate buffer at 37ºC), and dissolution efficiencies were also analyzed. The in-vitro dissolution study was performed on the brands, according to FDA,USP dissolution profile in three different PH (1.2), (4.5), and (6.8) at37ºC, using the USP apparatus II, then f1, f2 were determined for the time intervals of 10, 15, 30, 45 and 60 minutes, and dissolution efficiencies were calculated. MINITAB 14 statistical program used for in vitro in vivo correlation, level A was done for reference product. Results: A non linear relation was established which is typical for immediate release formulation, of class 1. There was significant relationship between in vitro and in vivo data of reference metronidazole product, Correlation and distribution of data with correlation coefficient (r=0.724, 0.837, 0.707), nonlinear relationship with p-value (>0.05) =(0.167, 0.098, 0.182), there is no out lines, no lake of fits at P-Values=0.0040, 006, 0.026. Conclusion: Study concluded that there is no linear correlation between percent of drug released and percent of drug absorbed ,this may be due to uncontrollable gastric emptying rate for class one Metronidazole. Peer Review History: Received 2 December 2019; Revised 10 January 2020; Accepted 28 February; Available online 15 March 2020 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Hayriye Eda Şatana Kara , Gazi University, Turkey, eda@gazi.edu.tr Dr. Mohamed Ismail Nounou , Appalachian College of Pharmacy, Oakwood, Virginia, USA, nounou@acp.edu